Search and seizure in terms of the Tax Administration Act 28 of 2011: the balance between taxpayer’s rights and tax collection - Van Zyl, Stephanus (University of Pretoria, 2021)
Mini Dissertation (LLM ( Taxation))--University of Pretoria, 2021.